Сreation and Development of Ethnic Theme Parks in Kazakhstan - SERGEYEVA, Aigul; TLEUBAYEVA, Aitolkyn; OMIRZAKOVA, Miroslava; AKIMOV, Zhaxylyk; DULATBEKOVA, Zhanar; ASKAROVA, Gulnash; ABDRAMANOVA, Gulzhan (Journal of Environmental Management and Tourism, 2020)
Ethnic tourism is an integral part of cultural and educational tourism. One of the priorities in ethnic tourism is the creation of ethnic theme parks (ethnic parks). Namely ethnic parks allow to learn about the traditions and culture of various ethnic groups directly by immersion to the environment. In developed countries, ethnic parks have become highly profitable activities in the tourism industry. This article discusses the potential for the development of ethnic tourism and creation of ethnic parks in Kazakhstan. The main directions and problems of the development of this field of activity are revealed. Current state of ethnocultural centers of the Republic of Kazakhstan is analyzed. In particular, examples from foreign practice are given. Recommendations are given on factors restraining the development of ethnic tourism and the creation of ethnic parks in Kazakhstan, a model for the development of national cultural tourism is proposed.